Australian and Canadian financial wellbeing policy landscape during COVID-19: An equity-informed policy scan - Ana Paula Belon; Aryati Yashadhana; Krystyna Kongats; Kayla Atkey; Nicole M. Glenn; Karla Jaques; Laura Nieuwendyk; Patrick Harris; Evelyne de Leeuw; Candace I.J. Nykiforuk (Elsevier, 2024)
Background: This targeted and comprehensive policy scan examined how different levels of governments in Australia and Canada responded to the financial crisis brought on by the COVID-19 pandemic. We mapped the types of early policy responses addressing financial strain and promoting financial wellbeing. We also examined their equity considerations. Methods: Through a systematic search, snowballing, and manual search, we identified Canadian and Australian policies at all government levels related to financial strain or financial wellbeing enacted or amended in 2019-2020. Using a deductive-inductive approach, policies were categorized by jurisdiction level, focal areas, and target population groups. Results: In total, 213 and 97 policies in Canada and Australia, respectively, were included. Comparisons between Canadian and Australian policies indicated a more diversified and equity-targeted policy landscape in Canada. In both countries, most policies focused on individual and family finances, followed by housing and employment areas. Conclusions: The policy scan identified gaps and missed opportunities in the early policies related to financial strain and financial wellbeing. While fast, temporary actions addressed individuals' immediate needs, we recommend governments develop a longer-term action plan to tackle the root causes of financial strain and poor financial wellbeing for better health and non-health crisis preparedness. Statement on Ethics and Informed Consent: This research reported in this paper did not require ethical clearance or patient informed consent as the data sources were published policy documents. This study did not involve data collection with humans (or animals), nor any secondary datasets involving data provided by humans (or from animal studies).